2021
DOI: 10.1021/acsami.1c10108
|View full text |Cite
|
Sign up to set email alerts
|

ZrW2O8/ZrO2 Composites with Low/Near-Zero Coefficients of Thermal Expansion Fabricated at Ultralow Temperature: An Integration of Hydrothermal Assembly and a Cold Sintering Process

Abstract: ZrW 2 O 8 /ZrO 2 composites with tunable low/nearzero coefficients of thermal expansion (CTE) are promising candidates in several fields including aerospace, precision manufacturing and measurement, electronic circuit, etc., for counteracting the thermal expansion effect. However, bottleneck issues (such as the unstable decomposition of ZrW 2 O 8 phase, manufacturing size limitation, etc.) caused by conventional hightemperature sintering impede the development and application of ZrW 2 O 8 /ZrO 2 . To solve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…So, the main mechanism behind the densification in the SnF 2 -based system may be the liquid phase formation followed by pressure solution creep and plastic deformation. Such a type of mechanism was reported for the ionic salts mechanically stressed at wet conditions. , The microstructures of all of the composites also show a similar kind of melting nature. Thus the microstructure and density confirm that liquid phase sintering accompanied by plastic deformation is the densification mechanism in SnF 2 -added composites.…”
Section: Resultssupporting
confidence: 57%
“…So, the main mechanism behind the densification in the SnF 2 -based system may be the liquid phase formation followed by pressure solution creep and plastic deformation. Such a type of mechanism was reported for the ionic salts mechanically stressed at wet conditions. , The microstructures of all of the composites also show a similar kind of melting nature. Thus the microstructure and density confirm that liquid phase sintering accompanied by plastic deformation is the densification mechanism in SnF 2 -added composites.…”
Section: Resultssupporting
confidence: 57%
“…Up to now, several cold sintering mechanisms have been reported, and the most accepted mechanisms include the “dissolution–precipitation” process and plastic deformation process 1,18,19 . The “dissolution–precipitation” process is driven by the mediate liquid phase and has been confirmed in many ceramics such as ZnO, Li 2 MoO 4 and BaTiO 3 1,20–23 . The plastic deformation is mainly affected by the external pressure that is proved by the material system of CaCO 3 and NaCl 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…1,18,19 The "dissolution-precipitation" process is driven by the mediate liquid phase and has been confirmed in many ceramics such as ZnO, Li 2 MoO 4 and BaTiO 3 . 1,[20][21][22][23] The plastic deformation is mainly affected by the external pressure that is proved by the material system of CaCO 3 and NaCl. 18,19 In the "dissolution-precipitation" process, the mediate liquid phase is selected based on the material system, which needs a certain solubility, and there are two types of dissolution: congruent dissolution where the composition of the precipitated solid has the same stoichiometry to the parent phase, and incongruent dissolution where the composition of the precipitated solid has a different stoichiometry with the parent phase.…”
Section: Introductionmentioning
confidence: 99%
“…Provided there is one phase that is the major volume fraction in the composite (the matrix) that can undergo sintering, other phases (the filler) can be integrated into the body and from the composite. [9][10][11][12][13][14] A range of works have demonstrated that novel phases and materials, such as polymers (thermoplastics and thermosets), [15][16][17][18][19][20] 2D materials, 21,22 and buckminsterfullerene, 23 can all be readily incorporated into the grain boundaries of a sintered ceramic material. Previously, a number of examples have been made of the cold sintering of low-loss dielectrics with other fillers.…”
Section: Introductionmentioning
confidence: 99%